(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Cerebral palsy (CP) is the most common motor neurodevelopmental disorder among children which incurs a huge economic burden in respect of treatment and rehabilitation. Aim: To assess the clinical profile of CP in the outdoors of tertiary level hospitals in Bangladesh. Methods: This cross-sectional study was carried out in two hospitals, namely Child Development Center, CMH Dhaka and Institute of Pediatric Neurodisorder and Autism, BSMMU, Dhaka from October 2019 to January 2020. A total of 134 cases were included by convenient sampling. Data were collected from the parents of the children by face to face interviews through a pretested semi-structured questionnaire. Results: CP was found more prevalent in male children (76.1%) than female children (23.9%). Most of the families (83.6%) belonging to CP children have monthly income ≤ Taka 24000.00. The majority of the parents were HSC qualified or less which accounted for 76.9% for father and 91.8% for mother respectively. Among the etiologies; perinatal asphyxia ranked highest (78.4%). The spastic variety was the most common (78.4%) presentation of which 41.0% suffered from quadriplegia. The majority of the CP cases (83.6%) were associated with intellectual disability. Conclusion: CP has a wide range of presentation, association and co-morbidities. Physicians should be aware of these diversified presentations and co-morbidities of CP and deal accordingly for better outcome of the patients. JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 19-21